Answer:
Step-by-step explanation:
The given H(x) = √(2 - 2x^2) can be decomposed as follows: 2 - 2x^2 is g(x), the input to f(x), which in turn is f(x) = √x.
Thus, f(x) = √x is the first function. Here the input is simply x.
g(x) = 2 - 2x^2 is the second function. We use this function now as the input to f(x). These operations create the new function H(x) = (f°g)(x) = √(2 - 2x^2).
In summary:
f(x) = √x
g(x) = 2 - 2x^2
Answer:
Two trains leave a town at the same time heading in opposite directions. One train is traveling 12 mph faster than the other. After two hours, they are 232 miles apart. What is the average speed of each train?
52 mph; 64 mph
55 mph; 70 mph
92 mph; 104 mph
98 mph; 110 mph
Step-by-step explanation:
Answer:
- f⁻¹(x) = (x + 1) / (x - 2)
- f⁻¹(1 ) = - 2
Step-by-step explanation:
<u>Given function:</u>
- f(x) = (2x + 1) / (x - 1)
<u>Find its inverse, substitute x with y and f(x) with x, solve for y:</u>
- x = (2y + 1) / (y - 1)
- x(y - 1) = 2y + 1
- xy - x = 2y + 1
- xy - 2y = x + 1
- y(x - 2) = x + 1
- y = (x + 1) / (x - 2)
<u>Substitute y with f⁻¹(x):</u>
- f⁻¹(x) = (x + 1) / (x - 2)
<u>Find f⁻¹(1 ):</u>
- f⁻¹(1 ) = ( 1 + 1) / (1 - 2) = 2 / - 1 = - 2
X intercept-(9,2/0)
y intercept-(0,-9)
hope this helps
The answer to 12x23 is 276